Fluid simulations of plasma turbulence at ion scales: Comparison with Vlasov-Maxwell simulations - Perrone, D.; Passot, T.; Laveder, D.; Valentini, F.; Sulem, P. L.; Zouganelis, I.; Veltri, P.; Servidio, S. (Physics of plasmas, 2018)
Comparisons are presented between a hybrid Vlasov-Maxwell (HVM) simulation of turbulence in a collisionless plasma and fluid reductions. These include Hall-magnetohydrodynamics (HMHD) and Landau fluid (LF) or finite Larmor radius-Landau fluid (FLR-LF) models that retain pressure anisotropy and low-frequency kinetic effects such as Landau damping and, for the last model, finite Larmor radius (FLR) corrections. The problem is considered in two space dimensions, when initial conditions involve moderate-amplitude perturbations of a homogeneous equilibrium plasma subject to an out-of-plane magnetic field. LF turns out to provide an accurate description of the velocity field up to the ion Larmor radius scale, and even to smaller scales for the magnetic field. Compressibility nevertheless appears significantly larger at the sub-ion scales in the fluid models than in the HVM simulation. High frequency kinetic effects, such as cyclotron resonances, not retained by fluid descriptions, could be at the origin of this discrepancy. A significant temperature anisotropy is generated, with a bias towards the perpendicular component, the more intense fluctuations being rather spread out and located in a broad vicinity of current sheets. Non-gyrotropic pressure tensor components are measured and are shown to reach a significant fraction of the total pressure fluctuations, with intense regions closely correlated with current sheets.